Pengaruh Electronic Word of Mouth dan Citra Merek Terhadap Niat Beli Produk Kecantikan Avoskin - Nanda Destyana Suci; Dorothy Rouly H. Pandjaitan; Nuzul Inas Nabila (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
In the 4.0 industrial era, internet development is increasing rapidly, which helps people easier to find information from product reviews on the internet. Based on that, the trend of product review content is booming on the internet. One of the beauty products primarily reviewed as content on the internet is the Avoskin product. In link with that condition, Because most people nowadays are supposed to listen to their friends or other people they think will understand better and see how well the image of a brand is, companies need to pay atention to the effect of ewom and brand image on purchase intention.This research is aimed to discover the effect of electronic word of mouth and brand image on the buying intention of Avoskin beauty products. The population in this research was the citizen of Bandar Lampung that recognized and were interested in purchasing Avoskin beauty products. This research was categorized as field research as the instrument of this research is questionnaires distributed to the respondents. 120 respondents made up the sample, which was selected by a purposive sampling method. The data were collected using a questionnaire that has been tested for validity and reliability. The data analysis in this study uses multiple linear regression. The results of this study imply that ewom and brand image significantly positively affect purchase intention.